2012
DOI: 10.1007/s00535-012-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of K-ras mutation status and subtypes in endoscopic ultrasound-guided fine-needle aspiration specimens from patients with unresectable pancreatic cancer

Abstract: K-ras mutation status and subtypes may be associated with survival duration in pancreatic cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 25 publications
6
79
1
Order By: Relevance
“…The activation of these pathways was involved in transformation, uncontrolled proliferation, invasion, and metastasis of pancreatic cancer cells (28). Detection of the Kras mutation status could be used to assess prognosis of pancreatic cancer (29)(30)(31). Moreover, the downstream targets of mutant Kras could also be used in the assessment of prognosis of pancreatic cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of these pathways was involved in transformation, uncontrolled proliferation, invasion, and metastasis of pancreatic cancer cells (28). Detection of the Kras mutation status could be used to assess prognosis of pancreatic cancer (29)(30)(31). Moreover, the downstream targets of mutant Kras could also be used in the assessment of prognosis of pancreatic cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that KRAS G12D and G12R mutations are negative prognostic factors for overall survival (Ogura et al, 2013). However, a second study found that the presence of KRAS G12R alone correlates with increased overall survival, whereas the KRAS G12D mutation resulted in the shortest overall survival (Faris et al, 2014).…”
Section: Ras Mutation Hotspots -Structural Biological and Functionalmentioning
confidence: 99%
“…Among patients with K-ras mutations, those with the G12V mutation had a significantly longer overall survival than those with the G12D or G12R mutations 20 . In our two cases, although we measured the K-ras mutation patterns of the pancreatic cancers, we were unable to distinguish which case had recurrent or second cancers.…”
Section: Discussionmentioning
confidence: 91%